Efektywnosc instytucjonalna krajow Unii Europejskiej w kontekscie globalnej gospodarki opartej na wiedzy - Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2014)
– The article is devoted to measuring the effectiveness of institutional systems of European Union countries in terms of their relevance to the requirements of the global knowledge-based economy. The theoretical analysis is based on the framework of new institutional economics with special consideration to economics of transaction costs. There are two main aims of the article. The main aim of the paper is to evaluate the progress obtained by Poland and the rest of so called New Member States of the European Union in the years 2000-2010 in the context of institutional reforms that can lead to decreasing of transaction costs and are up to requirements of global knowledge-based economy. The second aim of the paper is the evaluation of influence of the last crisis of the year 2008 on the institutional reforms in 'old' Europe. The realisation of that aims was possible due to application of TOPSIS method for the analysis of institutional effectiveness of European Union members states in the years 2000-2010. The empirical research is based on the data from Fraser Institute database for Economic Freedom.
Keywords: D02; O1; F6; C38; 330; institutional economics; effectiveness of institutional system; TOPSIS method; global knowledge-based economy; European Union